Bioequivalence studies of film-coated tablet and chewable tablet generic formulations of montelukast in healthy volunteers - Cánovas, Mercedes; Arcabell, Marta; Martínez, Gemma; Canals, Mireia; Cabré, Francesc (Arzneimittelforschung, 2011)
Two studies were conducted in order to assess the bioequivalence of montelukast (CAS 151767-02-1) 10 mg film-coated tablet (FCT) and 5 mg chewable tablet (CT) test formulations in comparison with the original brands. Under fasting conditions, healthy male and female volunteers received one 10 mg FCT or 5 mg CT orally as a single dose of a test or reference formulation. Both studies were designed as open-label, randomized, two-period, two-sequence, crossover studies with a 7-day washout interval. Plasma samples were collected up to 24 h after drug administration and montelukast levels were determined by a validated LC/MS/MS method. Pharmacokinetic parameters were calculated using non-compartmental analysis and were statistically compared by analysis of variance for test and reference formulation. Bioequivalence between products was determined by calculating 90% confidence interval of the ratio test/reference of least-square means of logarithmically transformed Cmax and AUC0–t parameters. AUC0–∞ was also analysed to obtain additional information. The calculated 90% confidence intervals for the ratios of Cmax and AUC0–t parameters were 89.33–110.52 and 92.06–109.46, respectively, in the FCT study, and 91.58–101.86 and 92.15–98.83, respectively, in the CT study, which are all within the bioequivalence acceptance range of 80–125%. Based on the results, it can be concluded that the evaluated test FCT and CT formulations are bioequivalent to their respective reference formulation in terms of rate and extent of absorption.
Keywords: Bioequivalence; CAS 151767-02-1; Healthy volunteers; Montelukast; Pharmacokinetics; Tablet